Evaluasi Kurikulum Pendidikan - Mohamad Mustafid Hamdi (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2020)
The curriculum is the spirit of the world of education, where the existence of a curriculum is always possible, and then what is an effective and efficient curriculum for our education which in fact is different from different cultures, ethnicities, races and religions? Curriculum evaluation has an important role in the world of education. Without an evaluation, we will not know the weaknesses and strengths in the planning and implementation process of the curriculum that has been used. And make this as feedback by interested parties, such as; parents, teachers, community curriculum developers, etc. So that it can be used as a reference for future curriculum improvement and development so that students are able to achieve the predetermined educational goals as effectively as possible. Curriculum evaluation approach using a scientistic ideal or an ideal humanistic. Principle: evaluation refers to objectives, is comprehensive, and objective. While the form of evaluation is formative evaluation and summative evaluation. Curriculum evaluation models: Measurement, Congruence, congruence, Illumination, and Educational System Evaluation. While the implementation of curriculum evaluation can use two kinds of techniques, namely: test and non-test techniques